Perancangan Dan Analisis Rangkaian Synchronous Boost Converter Untuk Penyalaan Lampu LED 21W Dengan Sumber Baterai 12VDC - Anugrah, Aldeni Prima; Anto, Budhi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Electronic devices efficiency is highly considered nowadays. One of the reasons caused low efficiency is power dissipation. Conventional Boost Converter has low efficiency, but there are some potentional area need to be improved. Synchronous Boost Converter is the improved method of Boost Converter to improve the Conventional Boost Converter efficiency. Design and simulation is supplied by 12VDC. 21W LED light as output consist of 21 strands of 1W LED. 21W LED light is supplied by 21VDC. Synchronous Boost Converter works in Discontinuous Conduction Mode (DCM) to generate 12VDC input to 21VDC output. Synchronous Boost Converter simulation shows 21W LED light power produces 82,22% efficiency which better 2,4207% than Conventional Boost Converter. Synchronous Boost Converter with lower frequency gives better efficiency, previous research with 30MHz produces 70-80% efficiency.Keywords: Synchronous Boost Converter, MOSFET, efficiency